Clustering Capital and Business through the Implementation of Corporate Strategy in the Amanah Belimbing Wuluh SME Group - Utomo, Yitno; Yunia Dwie Nurcahyanie; M. Nushron Ali Mukhtar; Manik Ayu Titisari; Jihan, Jelita Citrawati (Tibuana, 2025)
Abstract-Small and Medium Enterprises (SMEs) became a trend when the Indonesian economy experienced a downturn. SMEs of Amanah Belimbing Wuluh is a micro sector that is only able to produce products and is able to sell its production to cover the needs of the economic cycle. The aim of this research is to measure the feasibility of capital using the Net Present Value (NPV) concept. Measuring capital feasibility with the Average Rate of Return (ARR) concept. Looking for clustering of company strategies in business development through capital budgeting. The research sample was 30 SMEs. Data analysis using K-Means Cluster. The research results based on the feasibility of SME capital using the Net Present Value (NPV) concept produce a positive value (NPV) of IDR. 344,869,146 so it can be said to be feasible. The feasibility of SME capital with the Average Rate of Return (ARR) concept is 44.12% annually above a discount factor of 16% so it can be said to be feasible for the turnover of SMEs business capital Amanah Belimbing Wuluh Dukuh Menanggal. Cluster analysis divides two groups of company strategies. Cluster 1 contains investment strategies that have the attributes; final investment, total investment and average investment. Cluster 2 contains a capital turnover strategy that has the Average Rate of Return attribute.